2010
DOI: 10.1021/bi100516e
|View full text |Cite
|
Sign up to set email alerts
|

Compound Ice-Binding Site of an Antifreeze Protein Revealed by Mutagenesis and Fluorescent Tagging

Abstract: By binding to the surface of ice crystals, type III antifreeze protein (AFP) can depress the freezing point of fish blood to below that of freezing seawater. This 7-kDa globular protein is encoded by a multigene family that produces two major isoforms, SP and QAE, which are 55% identical. Disruptive mutations on the ice-binding site of type III AFP lower antifreeze activity but can also change ice crystal morphology. By attaching green fluorescent protein to different mutants and isoforms and by examining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 49 publications
5
118
0
Order By: Relevance
“…All proteins were labeled with TRITC except for nfeAFP8 (row viii), which was labeled with Pacific Blue. [12]. The difference in binding ability can be traced to amino acid changes on the portion of the IBS that binds to the primary prism plane of ice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All proteins were labeled with TRITC except for nfeAFP8 (row viii), which was labeled with Pacific Blue. [12]. The difference in binding ability can be traced to amino acid changes on the portion of the IBS that binds to the primary prism plane of ice.…”
Section: Discussionmentioning
confidence: 99%
“…1). Fluorescence-based ice plane affinity (FIPA) analysis has demonstrated that nfeAFP6 adsorbs solely to a pyramidal plane of ice and is incapable of arresting ice growth at undercooling temperatures [12].…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid residues of the IBS have frequently been identified via mutagenesis studies. 50,66,67 Mutations of amino acids that are important for ice binding result in a large reduction of thermal hysteresis activity. For example, the Thr and Ala residues that are important for ice binding of wfAFP-I are all located on one relatively flat and hydrophobic side of the a-helix.…”
Section: -58mentioning
confidence: 99%
“…69 While for most IBPs the IBS is localized on one face of the protein that can bind to either one or several ice crystal plane(s), in some cases, a "compound" IBS is identified. 59,67 Type III AFP from notched fin eel pout and ocean pout have an IBS composed of two regions positioned at an angle of roughly 150 with respect to each other. One binds the primary prism plane of ice; the other a pyramidal plane [ Fig.…”
Section: -58mentioning
confidence: 99%
“…That is, the QAE-2 isoform nfeAFP11 can only shape ice crystals, but has no TH activity, while its triple mutant nfeAFP11-V9Q/V19L/G20V (denoted nfeAFP11-tri) perfectly exhibits both activities. These residues were thought to construct a "compound" ice-binding site (IBS) that consists of two adjacent flat surfaces inclined at an angle of approximately 150° to each other (Garnham et al 2010). To determine if the triple mutations in nfeAFP11 led to changes in the structure of the IBS that could affect its icebinding activity, the multidimensional NMR spectra of both nfeAFP11 and nfeAFP11-tri were examined.…”
mentioning
confidence: 99%